(untitled) (GnosisWisdom, 2025)
The present study critically reviews the role of economic blocs in global food trade, a key but often underestimated aspect of food geopolitics. A systematic search of international scientific databases was conducted, identifying 25 relevant studies published between 2020 and 2025, based on an initial search of 150 references in databases such as Scopus, Web of Science, ScienceDirect, SpringerLink and Google Scholar using English language keywords, references that were classified based on the requirements of Preferred Reporting Items for Systematic reviews and Meta-Analyses. Economic blocs have patterns in common in that they promote intra-bloc trade but may exclude third parties through non-tariff rules. Structural effects of blocs on international food trade (these economic blocs have redefined global food trade, not only by eliminating internal tariff barriers, but also by imposing new forms of external regulation) 2. Impact on food sovereignty and security (food sovereignty, understood as the right of peoples to define their own agricultural and food policies, has been eroded by the logic of blocs) 3. Tensions between regionalism and multilateralism (the rise of economic blocs has been paralleled by an erosion of classical multilateralism, represented by the World Trade Organization). In conclusion, economic blocs are key players in the food trade architecture, so understanding how they work is essential for designing more inclusive policies.